A novel perspective for Lactobacillus reuteri: Nanoencapsulation to obtain functional fish fillets - Ceylan, Zafer; Uslu, Emin; Ispirli, Humeyra; Meral, Raciye; Gavgali, Mehmet; Yilmaz, Mustafa Tahsin; Dertli, Enes (ELSEVIER, 2019)
Enrichment of food products with beneficial Lactic Acid Bacteria (LAB) is an important methodology used to develop functional food products. Lactobacillus reuteri E81 was successfully nanoencapsulated into poly (vinyl alcohol)-based nanofibers for its application to the surface of fish fillets. The Scanning Electron Microscopy analysis confirmed the nanoencapsulation of L. reuteri E81 in electrospun nanofibers (LRNF) that had an average diameter of 381.83 +/- 130.69 nm. LAB growth in rainbow trout fillets and fatty fish (mackerel) and were found to be 2.92 and in the range of 3.27 and 2.66 log CFU/g, respectively. Importantly, the antioxidative characteristics of fish fillets significantly increased following their coating with LRNF. The results revealed a significant increase in the inhibition of free radicals in the samples treated with nanoencapsulated L. reuteri as compared to control group fish fillet samples. DPPH activity significantly increased to 40.24%, 44.96%, 44.97 in mackerel samples treated with nanoencapsulated L. reuteri (MLR) and increased to 19.76%, 20.87%, 21.46% in rainbow samples treated with nanoencapsulated L. reuteri (RLR). MLR samples exhibited the highest ABTS radical-scavenging activity (1631 mu mol TEAC/g). FRAP value of MLR samples was found to be 1.70 times higher than the control group samples.
Keywords: Lactobacillus reuteri E81; Functional fish fillet; Lactic acid; Antioxidative; Electrospinning; ANTIOXIDANT ACTIVITY; MICROBIOLOGICAL STABILITY; PROBIOTIC PROPERTIES; PHENOLIC-ACIDS; CHUB MACKEREL; FOOD; FERMENTATION; BACTERIA; STORAGE; POWER; Food Science & Technology